Hacking exposed Windows - Scambray, Joel (McGraw-Hill, 2008)
Meet the challenges of Windows security with the exclusive Hacking Exposed "attack-countermeasure" approach. Learn how real-world malicious hackers conduct reconnaissance of targets and then exploit common misconfigurations and software flaws on both clients and servers. See leading-edge exploitation techniques demonstrated, and learn how the latest countermeasures in Windows XP, Vista, and Server 2003/2008 can mitigate these attacks. Get practical advice based on the authors' and contributors' many years as security professionals hired to break into the world's largest IT infrastructures